Inflammation markers as risk factors of edematous pancreatitis development providing of genetic determination of IL-4 production - S. I. Ivashchuk; L. P. Sydorchuk (Journal of Education, Health and Sport, 2017)
Introduction. The powerful mechanism of the immune system involvement in the pathogenesis of acute pancreatitis (AP) and exacerbation of chronic pancreatitis (ECP), especially from the positions of influence of polymorphism of genes which regulate the inflammatory response (interleukin -1β (IL-1β), -4 (IL-4), -6 (IL -6) and tumor necrosis factor-alpha (TNF-α), and others.) on the clinical course of pancreatitis still stays outside the attention of researchers.